KEANEKARAGAMAN HAYATI DALAM MENUNJANG KETAHANAN PANGAN - Triyono, Kharis - (Innofarm:Jurnal Inovasi Pertanian, 2013)
ABSTRACTS Indonesia become the one of biodiversity center in the world and it is known as the megabiodiversity country. It is as natur wealth which can be useful at recent or in the fiture. The problems of providing food will become the one of main challenge of development, because of population always increase. Actually biodiversity in Indonesia as â€œEmas hijauâ€ which can be used as alternative to cope the problems of providing food. Althought biodiversity the latest in fact is :1) it is abundant yet we are poor of knowledge 2) it is potensial but it is not discovered and useless 3) it has future chances, yet we abandoned it. Keywords : Biodiversity, problems of providing food, food security Â